Kepemimpinan dalam Peningkatan Kualitas Pelayanan Publik di Daerah - Susilawati Susilawati; Eljawati Eljawati; Gradiana Tefa; Siti Nuraisyah Suwanda; Dadang Suwanda (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Garbage as a elementary problem of human life in forward territory, raises the handling urgency through providing performance of public service in hygine which is the success depends on leadership of a leader. This research uses quantitative methods with descriptive approach. Determination of research sample through multistages random sampling method and formulating them into Slovin formula. Research results show that the measurement of service quality in hygiene in the Jatinangor District Sumedang Regency is 65.30% or 3918 with good predicate. Measurement of Head of Subdistrict’s leadership in Jatinangor Subdistrict Sumedang Regency is 65.30% or 3918 with good predicate. As well as there is assosiation of Head of Subdistrict’s leadership towards service quality of hygiene in managing waste at the Jatinangor District with τ = np-nn/C(n,2) = 0.56.